2017
DOI: 10.1039/c7ra06073d
|View full text |Cite|
|
Sign up to set email alerts
|

Photodynamic antimicrobial chemotherapy with cationic phthalocyanines against Escherichia coli planktonic and biofilm cultures

Abstract: Cationic phthalocyanines (Pcs) combine with photodynamic antimicrobial chemotherapy (PACT) presents excellent antibacterial activity to Gram-negative bacteriaE. coli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…Interestingly, Li et al reported a comparative study to investigate the effects of charge on aPDT activity using two poly-cationic zinc-phthalocyanines (ZnPc) conjugated to mono-and di-amino moieties (formal charges of +4, +8) against the Gram− bacteria E. coli. As expected, the more highly charged ZnPc derivatives exhibited better inactivation efficacy [33].…”
Section: Conjugation Of Small Cationic Groups For Electrostatic Intersupporting
confidence: 73%
“…Interestingly, Li et al reported a comparative study to investigate the effects of charge on aPDT activity using two poly-cationic zinc-phthalocyanines (ZnPc) conjugated to mono-and di-amino moieties (formal charges of +4, +8) against the Gram− bacteria E. coli. As expected, the more highly charged ZnPc derivatives exhibited better inactivation efficacy [33].…”
Section: Conjugation Of Small Cationic Groups For Electrostatic Intersupporting
confidence: 73%
“…Moreover, all the results in the current study were acquired as the final effects of antimicrobial activity through MTT assay, CFU analysis, fluorescent, and SEM images. Therefore, more advanced quantitative methods such flow cytometry should be employed for the detection of ROS production during the treatment [ 10 , 11 , 40 ] to further validate the current findings. The exact function of endogenous intracellular porphyrins in the disinfection process resulting from 405-nm exposure should be fully elucidated.…”
Section: Discussionmentioning
confidence: 80%
“…Healthcare-associated infections (HAIs) have increasingly become problematic in the endoscopic procedures resulting in several severe diseases such as CRE-related infections, pneumonia, and bacteremia. However, many previous studies have agreed that some bacterial strains are currently resistant to traditional antimicrobials [ 10 , 11 ]. They have adopted various mechanisms to improve their resistance towards disinfectants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations